2020
DOI: 10.1037/fam0000643
|View full text |Cite
|
Sign up to set email alerts
|

When poor communication does and does not matter: The moderating role of stress.

Abstract: Although a number of theoretical perspectives in relationship science argue that variability in couples' relationship satisfaction over time is driven by changes in their communication, tests of this hypothesis have been limited to single assessments of behavior. To address this gap, we examine within-couple, across-time changes in communication, and we argue further that couples' external circumstances might combine with these behavioral changes to generate changes in relationship satisfaction. Using self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 48 publications
3
27
1
2
Order By: Relevance
“…Two other studies examined lagged associations between communication and satisfaction. Using the same sample as Nguyen et al (2020), Lavner and colleagues (2016) found no consistent pattern linking negative, positive, or effective communication with later relationship satisfaction. Among the 36 longitudinal communication-to-satisfaction paths estimated with all four waves of data (9-month lags), only seven were significant, and all cross-lagged links were small in magnitude.…”
Section: Previous Research Examining Within-person Linkages Between Communication and Relationship Satisfaction: Review And Critiquementioning
confidence: 95%
See 3 more Smart Citations
“…Two other studies examined lagged associations between communication and satisfaction. Using the same sample as Nguyen et al (2020), Lavner and colleagues (2016) found no consistent pattern linking negative, positive, or effective communication with later relationship satisfaction. Among the 36 longitudinal communication-to-satisfaction paths estimated with all four waves of data (9-month lags), only seven were significant, and all cross-lagged links were small in magnitude.…”
Section: Previous Research Examining Within-person Linkages Between Communication and Relationship Satisfaction: Review And Critiquementioning
confidence: 95%
“…To our knowledge, only three studies have sought to explicitly examine within-person associations between couple communication and relationship satisfaction with repeatedmeasures longitudinal data. The first study of these three drew on four waves of observational data gathered across the first 3 years of marriage among socioeconomically disadvantaged newlywed couples (Nguyen et al, 2020) to examine whether within-person fluctuations in positive (e.g., being affectionate), negative (e.g., showing contempt), and effective (e.g., generating solutions) observed communication covaried with concurrent fluctuations in relationship satisfaction and whether these results were moderated by stress. Results revealed husbands and wives were more satisfied than was typical for them at times when positive communication was higher than normal.…”
Section: Previous Research Examining Within-person Linkages Between Communication and Relationship Satisfaction: Review And Critiquementioning
confidence: 99%
See 2 more Smart Citations
“…Second, managing external stress depletes the energy and resources needed for people to effectively manage relationship problems (Buck & Neff, 2012). The more people are facing stressful events, the more they behave in blaming, critical and hostile ways (Barton & Bryant, 2016;Barton et al, 2015;Bodenmann et al, 2015;Masarik et al, 2016;Neff & Karney, 2004Williamson et al, 2013), which in turn predicts declines in relationship quality (Barton et al, 2015;Neff & Karney, 2004;Nguyen et al, 2020). Thus, people facing greater stress during COVID-19 quarantines should experience greater relationship problems, Figure 1.…”
Section: External Stress and Vulnerability X Stress Interaction Effectsmentioning
confidence: 99%